Essays on the Spread of Humanistic and Renaissance Literary Civilization in the Slavic World (15th-17th Century) - Siedina, Giovanna (Biblioteca di Studi Slavistici, 2020)
The essays gathered in this volume are devoted to different aspects of the reception of Humanism and the Renaissance in Slavic countries. They mark the beginning of a dialogue among scholars of different Slavic languages and literatures, in search of the ways in which the entire Slavic world - albeit to varying degrees - has participated from the very beginning in European cultural transformations, and not simply by sharing some characteristics of the new currents, but by building a new identity in harmony with the changes of the time. By overcoming the dominant paradigm, which sees all cultural manifestations as part of a separate 'national' linguistic, literary and artistic canon, this volume is intended to be the first step in outlining some ideas and suggestions in view of the creation, in the future, of an atlas that maps the relevance of Humanism and the Renaissance in the Slavic world.